Variability in open pollinated seedlings of black pepper (Piper nigrum L.) - SASIKUMAR, P N RAVINDRAN, B (Journal of Spices and Aromatic Crops, 1993)
Highly heterogeneous variances were observed for plant height, leaf number, leaf width, internode len gth and stem girth in open pollinated seedlings of three black pepper (Piper nigrum) cultivars. Collection 1344 had maximum range and coeffici ent of variation for all the characters followed by Panniyur-1 and a Karimunda Selection KS-27. Eighteen di stinct morphological variants were also recorded in the progeny of Coll. 1344. In some of the progenies, the initial variation sustained wi th growth for most of the morphological features. No such morphological variants were observed in the progenies ofPanniyur-1 and KS-27. The reason for this behaviour of the cultivar is di scussed.